Pengaruh Kualitas Produk Terhadap Keputusan Pembelian Handphone Oppo Di Kota Pagar Alam - Aldini Nofta Martini; Ahmad Feriyansyah; Sella Venanza (Nusa Putra University, 2021)
This study aims to determine whether there is an influence of product quality on purchasing decisions and to find out how big the product quality variable is on purchasing decisions. This research uses associative research. There are two variables used in this study, namely Product Quality (X) and Purchase Decision (Y). This data collection was obtained through distributing questionnaires directly to consumers of Oppo Mobile Products at the Artha Jaya Counter in Kota Pagar Alam. The sample used in this study were 93 respondents using simple linear statistical analysis techniques and sampling techniques. The results of the simple linear regression analysis test in this study indicate that Product Quality has a positive effect on purchasing decisions can be seen from the results of a simple regression analysis, namely: Y = 16.905 + 0.616 where the constant value of 16.905 the value of the Product Quality regression coefficient has a positive effect which means that if the Product Quality increases by one unit, the Purchase Decision will increase by 0.616 units. Product Quality has a significant effect on the Purchase Decision of Oppo Mobile products in Kota Pagar Alam which can be seen from the results of the t test where the significant value is 0,000, which means it is smaller than 0.05 so that the hypothesis is accepted.